Multiomic analyses reveal transcription factors involved in the fatty acid biosynthesis pathway under cold stress in upland cotton (Gossypium hirsutum) - Yang, Ni; Gong, Zhaolong; Li, Zihui; Zheng, Juyun; Liu, Zhi; Wang, Binyue; Geng, Shiwei; Sun, Fenglei; Chen, Haihong; Li, Shengmei; Wang, Junduo; Liang, Yajun (Frontiers in Plant Science, 2025)
IntroductionChromatin accessibility is broadly implicated in plant abiotic stress responses; nevertheless, its role under cold stress in upland cotton (Gossypium hirsutum) remains largely unexplored.MethodsHere, we integrated the transcriptomic, metabolomic, and ATAC-seq profiles of a cold-tolerant line, Xinluzao 52 (X52), and a cold-sensitive line, Dai 4554 (D4554), which were sampled before (0 h) and after (6 h) cold treatment.ResultsCompared with the respective 0-h controls, the 6-h cold exposure group had specifically enriched differentially expressed genes (DEGs) related to the fatty acid metabolism pathway in X52, while no comparable enrichment was observed in D4554. Among all the DEGs from comparison groups D4554-C vs. X52-C, D4554-C vs. D4554-T, D4554-T vs. X52-T, and X52-C vs. X52-T, a total of 3, 338 differentially expressed transcription factors (TFs) were identified, of which the MYB, bHLH, NAC, and WRKY families were predominated. Coexpression analysis partitioned these TFs into nine modules and identified 24 hub TFs. Metabolomic profiling revealed that fatty acids accounted for ~10% of the differentially expressed metabolites (DEMs), and eight of the nine TF coexpression modules were strongly correlated with fatty acid pathway metabolites (|r| > 0.9, P < 0.01). ATAC-seq detected 92, 356 differentially accessible regions (DARs) in X52 (0 h vs. 6 h). Genes linked to these DARs were significantly enriched for DNA-binding and DNA-templated transcription functions. In addition, DAR-linked genes were annotated to lipid metabolism. Notably, the DARs were enriched for binding motifs of bHLH-, bZIP-, AP2-, and C2H2-type TFs. In summary, we elucidate a chromatin accessibility–TF–enzyme gene–fatty acid metabolite regulatory network and highlight the possible chromatin-mediated transcriptional control of fatty acid metabolism during the adaptation to cold stress in cotton, offering a new perspective on the molecular basis of cold tolerance in upland cotton.